Kegiatan Penapisan Pemeriksaan Gula Darah Sewaktu terhadap Penyakit Diabetes Mellitus Tipe 2 pada Populasi Lanjut Usia di Panti Werda Hana - Ernawati Ernawati; Marendra Shinery Kartolo; Fladys Jashinta Mashadi; Yovian Timothy Satyo; Junius Kurniawan (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Insulin and glucagon, hormones secreted by the pancreas, regulate blood glucose, the main source of energy for cells. Insulin facilitates glucose uptake and glycogen synthesis, whereas glucagon increases blood glucose by stimulating glycogenolysis and gluconeogenesis in the fasting state. An increase in blood glucose above normal over a long period of time can cause diabetes mellitus. The prevalence of type 2 diabetes among the elderly in Indonesia is 6.2%, with a projected increase to 12 million cases by 2030. The causes include genetic factors, aging, unhealthy eating patterns, a lack of movement, and comorbidities such as obesity and hypertension. This activity uses the PDCA (Plan-Do-Check-Action) method, which aims to carry out blood glucose checks as an early detection of type 2 diabetes mellitus. The Hana Nursing Home in South Tangerang hosted this activity, which involved 61 participants. The results of the blood glucose examination showed that 15 people (24.58%) had diabetes and 33 people (54.1%) had pre-diabetes. Early detection and effective management are essential to prevent complications and maintain functional status.